2007
DOI: 10.1093/rheumatology/kel170
|View full text |Cite
|
Sign up to set email alerts
|

The PTPN22 C1858T functional polymorphism and autoimmune diseases--a meta-analysis

Abstract: This meta-analysis demonstrates that the PTPN22 1858T allele confers susceptibility to RA, SLE, GD, T1D and JIA, supporting evidence of association of the PTPN22 gene with subgroup of autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
187
1
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(204 citation statements)
references
References 53 publications
10
187
1
6
Order By: Relevance
“…Their presumed low-expression or low-activity genotypes predispose to multiple autoimmune diseases, including type 1 diabetes, [5][6][7][8][9] Graves' disease, 7,8 hypothyroidism, 6,8 systemic lupus erythematosus, 6,10 rheumatoid arthritis, 6,11 and non-thymoma myasthenia gravis (MG). 12 However, the function of PTPN22 in this tolerance failure 13 has become debatable because of the paradoxically stronger inhibition of T-cell activation 14 by the autoimmunity-prone PTPN22 þ 1858T/T ( 620 W) or C/T genotype rather than the protective þ 1858C/C ( 620 R). A previous study on French subjects showed an association of the PTPN22 þ 1858C/T single nucleotide polymorphism with non-thymoma MG without anti-titin antibodies but not with thymoma-associated MG. 12 It has been found that interleukin-2 (IL-2) is expressed in the thymus during T-cell receptor (TCR)-mediated thymocyte apoptosis, and IL-2/IL-2 receptor (IL-2R) signaling is required for intrathymic negative selection of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Their presumed low-expression or low-activity genotypes predispose to multiple autoimmune diseases, including type 1 diabetes, [5][6][7][8][9] Graves' disease, 7,8 hypothyroidism, 6,8 systemic lupus erythematosus, 6,10 rheumatoid arthritis, 6,11 and non-thymoma myasthenia gravis (MG). 12 However, the function of PTPN22 in this tolerance failure 13 has become debatable because of the paradoxically stronger inhibition of T-cell activation 14 by the autoimmunity-prone PTPN22 þ 1858T/T ( 620 W) or C/T genotype rather than the protective þ 1858C/C ( 620 R). A previous study on French subjects showed an association of the PTPN22 þ 1858C/T single nucleotide polymorphism with non-thymoma MG without anti-titin antibodies but not with thymoma-associated MG. 12 It has been found that interleukin-2 (IL-2) is expressed in the thymus during T-cell receptor (TCR)-mediated thymocyte apoptosis, and IL-2/IL-2 receptor (IL-2R) signaling is required for intrathymic negative selection of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…The protein tyrosine kinase non-receptor (PTPN22) gene has been confirmed as a second RA susceptibility gene in white Caucasian populations, increasing the risk of RA by 40-70%. Interestingly, the variant has not been found in Far Eastern populations (8). Both the HLA-DRB1 and PTPN22 genes are important in immune function and both predispose to other autoimmune diseases, such as type 1 diabetes and systemic lupus erythematosus, as well as RA (9).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed since Bottini et al (17) first discovered the influence of the PTPN22 gene on autoimmune diseases (17). PTPN22 is a strong inhibitor of T cell activation and may therefore affect susceptibility to autoimmunity; it has been implicated in a number of autoimmune and inflammatory diseases (17,27,28).…”
Section: Discussionmentioning
confidence: 99%